My friend Leonard - Frey, James (New York : Riverhead Books, 2005)
A personal account about the author's relationship with Leonard, the father figure from A Million Little Pieces, recounts how Leonard helped him recover from drug and alcohol addictions and then encouraged him to pursue a writing career before mysteriously disappearing.
Keywords: Frey, James, -- 1969- -- Friends and associates; Recovering addicts -- United States -- Biography; Ex-convicts -- United States -- Biography